2007
DOI: 10.1074/jbc.c700190200
|View full text |Cite
|
Sign up to set email alerts
|

Gain-of-function Mutation in TRPML3 Causes the Mouse Varitint-Waddler Phenotype

Abstract: TRPML3 is a member of the TRPML subfamily of the transient receptor potential cation channel superfamily. The TRPML3(A419P) mutation causes a severe form, whereas the TRPML3(I362T/A419P) mutation results in a mild form of the varitint-waddler phenotype. The channel properties of TRPML3 and how the mutations cause each phenotype are not known. In this study, we report the first channel properties of TRPML3 as a strongly inward rectifying cation channel with a novel regulation by extracytosolic Na ؉ . Preincubat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
148
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 111 publications
(159 citation statements)
references
References 9 publications
11
148
0
Order By: Relevance
“…After incubation in Na þ -free solution, pH 7.4, re-application of Na þ o results in a transient, rapidly inactivating current by TRPML3(H283R), which is inhibitable by H þ e-cyto . These TRPML3(H283A) properties are the same as those reported for TRPML3(A419P) (Kim et al, 2007). To further compare between the two mutants, we measured their effect on cell survival and plasma membrane Ca 2 þ permeability.…”
Section: Regulation Of Trpml3 By H þsupporting
confidence: 52%
See 4 more Smart Citations
“…After incubation in Na þ -free solution, pH 7.4, re-application of Na þ o results in a transient, rapidly inactivating current by TRPML3(H283R), which is inhibitable by H þ e-cyto . These TRPML3(H283A) properties are the same as those reported for TRPML3(A419P) (Kim et al, 2007). To further compare between the two mutants, we measured their effect on cell survival and plasma membrane Ca 2 þ permeability.…”
Section: Regulation Of Trpml3 By H þsupporting
confidence: 52%
“…Recently we (Kim et al, 2007) and others (Grimm et al, 2007;Xu et al, 2007;Nagata et al, 2008) reported that the varitintwaddler phenotype is caused by a GOF that makes TRPML3(A419P) spontaneously active, as found with TRPML3(H283A). Moreover, both mutants similarly increase plasma membrane Ca 2 þ permeability and reduce cell survival in a Ca 2 þ -dependent manner ( Figure 3E and F).…”
Section: Molecular Mechanism Of the Gof By Trpml3(a419p)mentioning
confidence: 73%
See 3 more Smart Citations